Teaching Counselling Theory and Skills: A Scoping Review of Canadian Graduate Counselling Psychology Coursework - Harris, Gregory E.; Flood, Katie A. (Canadian Journal of Counselling and Psychotherapy, 2015)
This article describes a scoping review and content analysis of Canadian counselling and counselling psychology graduate coursework focused on counselling and psychotherapy preparation. The authors explored the coursework of 24 graduate-level master’s programs and received relevant syllabi from 11 of these programs. Through a content analysis framework, multiple themes were identified, including areas such as course description, objectives, structures, expectations, readings, and evaluations/assignments. Implications for teaching and training are discussed along with considerations for future research.